Implementation of Problem based Learning Models to Improve Thinking Ability Student Criticism Reviewed from Learning Style - Harahap, Irham Habibi (Universitas Muhammadiyah Surakarta, 2024)
The development of students' critical mathematical thinking skills and attention to individual uniqueness in the learning process needs to be given attention, in order to be able to create an inclusive learning environment and support the development of each student's potential. The aim of this research is to determine the differences in the achievement and improvement of students' critical mathematical thinking skills from two different learning models and based on learning styles. The experimental group used a problem-based learning approach, while the control group used a conventional learning approach. This research uses a quantitative quasi-experimental method with a pre-test and post-test non-equivalent group design. This data was collected through a mathematical critical thinking ability test and a learning style questionnaire, which were completed by 40 students of SMP Swasta Sriwijaya Medan. The results of this study showed that students who took part in problem-based learning, as well as students with a kinesthetic learning style, performed better compared to the group who took part in conventional learning. However, if you look at auditory and kinesthetic learning styles, students who take part in problem-based descriptive learning have better performance. Therefore, it can be concluded that problem-based learning is quite effective in developing critical mathematical thinking skills, especially for students with a kinesthetic learning style.